Home is where my heart is - Saslim, Clarita (Nanyang Technological University, 2020)
Home Is Where My Heart Is is an immersive installation that serves as a figurative physical repository of the artist’s memories and experiences, a self-portrait through objects and sound. It features found and personal objects procured from Jakarta and Singapore, and a soundscape playing through multiple speakers hidden in or around the suspended objects. The sounds were mostly recorded live in Jakarta and Singapore, through foley, or sourced from online open-sourced sound libraries. Set up in an outdoor sheltered area, the surrounding environmental and human sounds also contribute to the soundscape and act as a live audio component, becoming part of the narrative. While the installation is a manifestation of private experiences, it also hopes to receive multiple interpretations influenced by the audience’s personal perceptions and associations of the objects and sounds. Thus, the installation hopes to be a space where the collective memory coexists with the personal, creating a network of shared and personal experiences rooted in and triggered by sonic and visual prompts.